Design of Affordable Cold Storage for Horticulture Products (Urban Farming “Mom's Farm” in Sampora Village) - Ferdian Suprata; Christine Natalia; Djoko Setyanto; Budi Kartadinata; Victoria Principall (Jurnal Ilmiah Teknik Industri, 2022)
Growing the world’s population to almost 9.7 billion by 2050 will continue to address the challenges facing the food and agriculture sector. The aim of this study is to reduce food losses in Sampora Village, Cisauk – South Tangerang by creating an affordable cold-storage of Modified Atmosphere Storage (MAS) equipment with a capacity of 4.77 m3 so that it can increase the quality of food for a longer period without deterioration of the horticultural products stored. Temperature control, humidity control, air circulation, maintenance of space between containers for adequate ventilation, total capacity, dimensions, efficiency, development costs, durability, performance, and features are involved in the design. This cold storage is designed with a Design Thinking method. A qualitative research was conducted through interviews to gain insight and synthesize the needs. The selection prototype concept was chosen by the Pugh Matrix and finally this study proposed in an affordable cold-storage technology.